2018
DOI: 10.1007/s00540-018-2558-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the volume of supra-inguinal injected solution on the spread of the injectate under the fascia iliaca: a preliminary study

Abstract: The fascia iliaca compartment is the compartment confined by the fascia iliaca (FI) and a muscular layer formed by the iliac-and psoas muscle. This compartment creates a virtual tunnel that contains the femoral nerve (FN), the obturator nerve (ON), and the lateral femoral cutaneous nerve (LFCN) of the lumbar plexus. In this pilot study, we aimed to determine the suggested volume needed to reach the three target nerves of the lumbar plexus (FN, ON, and LFCN) with a single-injection ultrasound-guided supra-ingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 12 publications
(10 reference statements)
1
32
0
1
Order By: Relevance
“…We read with great interest the article from Vermeylen about suprainguinal fascia iliaca compartment block (SFICB) [1].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article from Vermeylen about suprainguinal fascia iliaca compartment block (SFICB) [1].…”
Section: To the Editormentioning
confidence: 99%
“…Ultrasound-guided FICB is a fascial block, with two possible approaches, infrainguinal or suprainguinal, aiming femorocutaneous, femoral and obturator nerves, all together in a single-shot technique [2]. Nevertheless, suprainguinal approach to FICB leads to a more consistent block of the three target nerves [1,2].…”
Section: To the Editormentioning
confidence: 99%
“…Correct needle placement is confirmed by separation of the fascia iliaca from the iliopsoas muscle with LA spreading towards the FN medially and the iliac crest laterally. 6 Volumes of 30e40 ml, ensuring compliance with safe dose limits for the LA, are routinely used to ensure optimal spread.…”
Section: Ultrasound Guided Infrainguinal Approachmentioning
confidence: 99%
“…A recent cadaveric study found that a volume of 40 ml was required to reliably block all three nerves using this approach. 6…”
Section: Ultrasound Guided Suprainguinal Approachmentioning
confidence: 99%
“…One of the anterior approach to the lumbar plexus block is supra-inguinal fascia iliaca compartment block (SI-FICB) [11,12]. This technique, theoretically, can block the femoral, obturator, and lateral femoral cutaneous nerves simultaneously, since these nerves are contained within the same compartment [13].…”
Section: Introductionmentioning
confidence: 99%